The potential of L. scoparium, K. robusta and P. radiata to mitigate N-losses in silvopastural systems. (June 2017) - Esperschuetz, J.; Balaine, N.; Clough, T.; Bulman, S.; Dickinson, N.M.; Horswell, J.; Robinson, B.H.
Abstract: Silvopastoral systems aim to enhance economic, cultural and social principles by sustainably combining forest management with agriculture. In these typically high-nitrogen (N) environments, plant species selection can profoundly influence N fluxes. For grazed pastures, plants may be exposed to urine patches that have received the equivalent of up to 1000 kg N ha −1 . We aimed to determine the growth and N fluxes in three potential trees that may be used in silvopastoral systems: L. scoparium, K. robusta and P. radiata . Plants were grown in a greenhouse lysimeter experiment, with controlled irrigation and temperature and exposed to N at rates of 200 kg ha −1 equiv. for 15 weeks, followed by the addition of 800 kg ha −1 N equiv, to simulate a urine patch. Urea produced a positive growth response of all plant species. Treatments containing L. scoparium and K. robusta leached lower amounts of nitrate (NO3 − ) (2 kg ha −1 NO3 − ) compared to P. radiata (53 kg ha −1 ). Measurements of N2 O over 20 days after the application of 800 kg N ha −1 indicated an inhibitory effect of L. scoparium and K. robusta on denitrification, hence loss of N via N2 O. Both L. scoparium and K. robusta demonstrated that they have potential to reduce N-losses in silvopastural systems, while producing valuable biomass. Graphical abstract: Highlights: Tree species selection in silvopastoral systems can minimize N losses. Mānuka, kānuka and pine respond positively to agricultural rates of N addition. Mānuka and kānuka reduce nitrate leaching after urea application compared to pine. Both mānuka and kānuka inhibit denitrification. Abstract : L. scoparium and K. robusta minimize N losses from leaching and N2 O emissions after urea application.